Observations of GW170817 by DESGW and the DECam GW-EM Collaboration. Issue Volume 13:Issue S338(2017) (29th January 2019) - Annis, James
Abstract: On August 17, 2017 LIGO/Virgo detected a binary neutron star via gravitational waves. We observed 70 sq-degrees in the LIGO/Virgo spatial localization with the DECam on the 4m Blanco telescope covering 80% of the final map. Our group independently discovered an optical counterpart in NGC 4993. We searched our entire imaged region: the object in NGC 4993 was the only viable candidate. Our observations of NGC4993 show complicated morphology but simple star formation history. Our x-ray and radio observations indicate an off-axis jet as afterglow. Our high-cadence optical and infrared spectra show a source that must be described by at least two components, one of which is dominated by the r-process nucleosynthesis elements characteristic of a kilonova. Our modeling of the light curve demonstrates such a model in which 0.05 M⊙ of material is ejected from the system. Finally, we discuss the first standard siren measurement of H0 .